Different expression of β subunits of the KCa1.1 channel by invasive and non-invasive human fibroblast-like synoviocytes. Issue 1 (December 2016) - Pethő, Zoltán; Tanner, Mark; Tajhya, Rajeev; Huq, Redwan; Laragione, Teresina; Panyi, Gyorgy; Gulko, Pércio; Beeton, Christine
Abstract Background Fibroblast-like synoviocytes (FLS) in rheumatoid arthritis (RA-FLS) contribute to joint inflammation and damage characteristic of the disease. RA-FLS express KCa1.1 (BK, Slo1, MaxiK, KCNMA1 ) as their major plasma membrane potassium channel. Blocking KCa1.1 reduces the invasive phenotype of RA-FLS and attenuates disease severity in animal models of RA. This channel has therefore emerged as a promising therapeutic target in RA. However, the pore-forming α subunit of KCa1.1 is widely distributed in the body, and blocking it induces severe side effects, thus limiting its value as a therapeutic target. On the other hand, KCa1.1 channels can also contain different accessory subunits with restricted tissue distribution that regulate channel kinetics and pharmacology. Identification of the regulatory subunits of KCa1.1 expressed by RA-FLS may therefore provide the opportunity for generating a selective target for RA treatment. Methods Highly invasive RA-FLS were isolated from patients with RA, and FLS from patients with osteoarthritis (OA) were used as minimally invasive controls. The β subunit expression by FLS was assessed by quantitative reverse transcription polymerase chain reactions, Western blotting, and patch-clamp electrophysiology combined with pharmacological agents. FLS were sorted by flow cytometry on the basis of their CD44 expression level for comparison of their invasiveness and with their expression of KCa1.1 α and β subunits. β1 and β3 subunit expression was reduced with small interfering RNA (siRNA) to assess their specific role in KCa1.1α expression and function and in FLS invasiveness. Results We identified functional β1 and β3b regulatory subunits in RA-FLS. KCa1.1 β3b subunits were expressed by 70 % of the cells and were associated with highly invasive CD44high RA-FLS, whereas minimally invasive CD44low RA-FLS and OA-FLS expressed either β1 subunit. Furthermore, we found that silencing the β3 but not the β1 subunit with siRNA reduced KCa1.1 channel density at the plasma membrane of RA-FLS and inhibited RA-FLS invasiveness. Conclusions Our findings suggest the KCa1.1 channel composed of α and β3b subunits as an attractive target for the therapy of RA.